ANALYZING THE PURCHASE INTENTION OF TUMBLER BY MILLENNIAL GENERATION IN MANADO - Mamahit, Meygitta Vanesa; Kalangi, Josep B.; Pandowo, Merinda H. C. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: The use of excessive plastic bottles is one of the causes of environmental problems. Social marketing is used as a strategy to change individual behavior towards sustainable consumption that does not damage the natural environment. One of the environmental care behaviors that is expected to minimize environmental problem due to plastic bottles which is using tumbler as the environmentally friendly products. This research aims to analyzing the purchase intention of tumbler by millennial generation in Manado using the Theory of Planned Behavior model (Attitude, Subjective Norms, Perceived Behavioral Control). This study uses quantitative method with causal analysis. Questionnaire is used to collect the data. This research derived and examined the model through multiple linear regression model in a sample of 150 millennials respondents in Manado. Finding of this research shows that attitude, subjective norms and perceived behavioral control influences purchase intention of tumbler by millennial generation in Manado significantly. From the results, it is recommended for the policy makers related to government and marketers to provide adequate information in campaigning the use of tumbler and educate the millennials about the benefit of tumbler. Keywords: theory of planned behavior, purchase intention, tumbler